The presence of wet- milk in breastfeeding of white children in the city of Sao Paulo in the nineteenth century - Silva, Robson Roberto [UNESP] (Univ Estadual Londrina, 2016)
The aim of this study is to analyze the participation of black women in social function of wet-milk in breastfeeding of white children of noble families in the city of Sao Paulo in the nineteenth century, because white mothers had no physical condition to ensure their feeding. The black slaves became known as women who because of their physical size and racial characteristics, could give the breast to the sons of lords. They were obliged to reject the breast milk their own offspring, which increased mortality rates among child slaves. But the performance of the wet-milk was not limited to the house of lords, in Sao Paulo, in many newspaper ads, they were rented in the cases of women who were unable to breastfeed. The freed black also rented their love-nurse services to get some money. The presence of wet-milk in infant feeding began to be challenged by the public health in the final decades of the nineteenth century; with the development of prophylactic and hygienic childcare. According to the scientific thinking of the late nineteenth century, medical criticism of the wet-milk would be due to poor hygiene in breastfeeding, causing disease and increased infant mortality, so that their services have been targets of political regulation of social control.
Keywords: Brazil Empire; Slavery; Love-nurse; Female slaves; Breast-feeding